MENYELESAIKAN VEHICLE ROUTING PROBLEM MENGGUNAKAN ALGORITMA FUZZY EVOLUSI - SUMADI, I PUTU ARYA YOGA; KENCANA, I PUTU EKA NILA; HARINI, LUH PUTU IDA (E-Jurnal Matematika, 2018)
The purpose of this research is to know the performance of Fuzzy Evolutionary Algorithm in solving one type of Vehicle Routing Problem that is Capacitated Vehicle Routing Problem (CVRP). There are 8 different CVRP data to be solved. The performance of the algorithm can be determined by comparing the value obtained by AFE with the optimal value of the data. The result of this research is fuzzy evolution algorithm yields the best average relative error from all data for distance that is equal to 69,5855% and for minimum vehicle equal to 26%.